Majority and minority voted redundancy scheme for safety-critical applications with error/no-error signaling logic - Balasubramanian, Padmanabhan (2018)
In the era of nanoelectronics, multiple faults or failures of function blocks are likely to occur. To withstand these, higher levels of redundancy are suggested to be employed in at least the sensitive portions of a circuit or system. In this context, the N-modular redundancy (NMR) scheme may be used to guard against the multiple faults or failures of function blocks. However, the NMR scheme would exacerbate the weight, cost, and design metrics to implement higher-order redundancy. Hence, as an alternative to the NMR, the majority and minority voted redundancy (MMR) scheme was proposed recently. However, the proposal was restricted to the basic implementation with no provision for indicating the correct or the incorrect operation of the MMR. Hence in this work, we present the MMR scheme with the error/no-error signaling logic (ESL). Example NMR circuits without and with the ESL (NMRESL), and example MMR circuits without and with the proposed ESL (MMRESL) were implemented to achieve similar degrees of fault tolerance using a 32/28-nm CMOS technology. The results show that, on average, the proposed MMRESL circuits have 18.9% less critical path delay, dissipate 64.8% less power, and require 49.5% less silicon area compared to their counterpart NMRESL circuits.